Perlindungan Hak Pekerja melalui Mekanisme Gugatan Perdata - Muhammad Rafly Passya; Muhammad Irsyad Al-Fahrizi; Gerald Ivanza Iskandar; Rizha Claudilla Putri (Lembaga Pengembangan Kinerja Dosen, 2026)
The protection of workers’ rights represents a constitutional mandate within Indonesia’s rule of law framework. Although the national labor law system provides a civil litigation mechanism through the Industrial Relations Court to resolve disputes, violations of workers’ rights still frequently occur in practice. This study aims to analyze, from normative and theoretical perspectives, the protection of workers’ rights through civil lawsuit mechanisms and to evaluate their effectiveness in achieving substantive justice. The research applies a normative juridical method using statutory, conceptual, and case approaches to examine relevant legal provisions and their implementation. The findings reveal that the civil litigation mechanism provides a clear legal basis for workers to pursue claims and defend their rights. However, its effectiveness in practice remains limited due to several challenges, including structural constraints within the legal system, complex procedural requirements, and unequal bargaining power between workers and employers. These conditions often hinder workers from obtaining fair outcomes. Therefore, policy reform, simplification of legal procedures, and stronger access to justice are necessary to ensure more effective and substantive protection of workers’ rights in Indonesia.